2018
DOI: 10.1016/j.jctb.2017.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Cycle lengths and minimum degree of graphs

Abstract: There has been extensive research on cycle lengths in graphs with large minimum degree. In this paper, we obtain several new and tight results in this area. Let G be a graph with minimum degree at least k + 1. We prove that if G is bipartite, then there are k cycles in G whose lengths form an arithmetic progression with common difference two. For general graph G, we show that G contains ⌊k/2⌋ cycles with consecutive even lengths and k − 3 cycles whose lengths form an arithmetic progression with common differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 34 publications
0
41
0
Order By: Relevance
“…The conjecture received new attention recently. In particular Liu-Ma [41] settled the case when h is even, and Diwan [24] proved it for m = 2. To date, Sudakov and Verstraëte [52] hold the best known bound for the general case on this problem.…”
Section: Proof Of Lemma 11mentioning
confidence: 97%
“…The conjecture received new attention recently. In particular Liu-Ma [41] settled the case when h is even, and Diwan [24] proved it for m = 2. To date, Sudakov and Verstraëte [52] hold the best known bound for the general case on this problem.…”
Section: Proof Of Lemma 11mentioning
confidence: 97%
“…Since then there has been an extensive research [15,32,26,28] on related topics. Very recently Liu and the second author [27] proved a tight result that every graph G with minimum degree at least 2k + 1 contains k cycles of consecutive even lengths; and if G is 2-connected and non-bipartite, then G also contains k cycles of consecutive odd lengths. Among others, one closely related problem is the study of cycle lengths modulo then immediately yields bounds on the Turán numbers of Berge cycles (for both even and odd cycles simultaneously).…”
Section: Introductionmentioning
confidence: 99%
“…• Thomassen [27] conjectured that every graph of minimum degree at least k + 1 contains cycles of all possible even lengths mod k. This conjecture was proved when k is even by Liu and Ma [19], and they showed further that there are cycles of k/2 consecutive even lengths in this case. Liu and Ma also showed that if k is odd and G is a graph of minimum degree at least k + 5, then G contains cycles of all even lengths mod k. It is natural to conjecture the following strengthening of Thomassen's conjecture [27]: Conjecture 8.…”
Section: Discussionmentioning
confidence: 99%
“…Thomassen [27] conjectured that every graph of minimum degree at least k + 1 contains cycles of all possible even lengths mod k. Since every graph with average degree a least 2k contains a subgraph of minimum degree at least k + 1, this conjecture implies that c k (ℓ) ≤ 2k when k is even. Recently, Liu and Ma [19] showed for k even that a graph of minimum degree at least k + 1 contains cycles of all possible even lengths mod k, answering a conjecture of Thomassen [27] for even values of k. Since any graph whose blocks are cliques of order k + 1 contains no cycle of length 2 modulo k, this is best possible.…”
Section: Introductionmentioning
confidence: 86%